Polarization Analysis of Type III Langmuir/Z-mode Waves with Coherent Magnetic Component Observations by Solar Orbiter - Tomáš Formánek; Ondřej Santolík; Jan Souček; David Píša; Arnaud Zaslavsky; Matthieu Kretzschmar; Milan Maksimovic; Christopher J. Owen; Georgios Nicolaou (The Astrophysical Journal Letters)
Observations from the Solar Orbiter spacecraft provide unique insights into the interaction between electron beams and the plasma background in the source regions of type III radio emissions. We analyze this interaction by examining the high-frequency electric and magnetic components of in situ wave measurements, focusing on their polarization properties. Using electron data from onboard instruments, we model the electron velocity distribution function and numerically solve the dispersion relation. We compare the predicted polarization of the electric and magnetic components with the observations. Our findings are consistent with propagation in the Langmuir/Z-mode at an oblique wavevector. We explain the magnetic component and transverse polarization by the presence of small density fluctuations, without the need for mode conversion.